(untitled) (Indonesian Minority Justice Review, 2024)
This paper examines the legal frameworks for protecting refugees and migrants in Indonesia, focusing on the challenges and opportunities within the current system. While Indonesia is a signatory to several international conventions on refugee protection, it has not ratified the 1951 Refugee Convention, leaving a gap in legal protections for asylum seekers. The research investigates the national laws, such as the Immigration Law and the 2016 Presidential Regulation on Refugee Protection, and assesses their ability to ensure the rights and safety of refugees and migrants. By reviewing case law, government policies, and interviews with NGOs and human rights organizations, the paper highlights key issues such as the lack of a clear asylum process, indefinite detention, and limited access to healthcare and employment for migrants. The paper finds that although Indonesia’s legal framework provides some protections, significant gaps remain in terms of enforcement, legal recognition, and the provision of basic services. The paper concludes by recommending comprehensive reforms, including ratification of the 1951 Refugee Convention, the establishment of a transparent asylum process, and better integration of refugees and migrants into society through access to education, healthcare, and employment.